1978
DOI: 10.1126/science.356262
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Maps of Human Gene Frequencies in Europeans

Abstract: Multivarate techniques can be used to condense the information for a large number of loci and alleles into one or a few synthetic variables. The geographic distribution of synthetic variables can be plotted by the same technique used in mapping the gene frequency of a single allele. Synthetic maps were constructed for Europe and the Near East, with the use of principal components to condense the information of 38 independent alleles from ten loci. The first principal component summarizes close to 30% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
472
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(501 citation statements)
references
References 6 publications
22
472
1
3
Order By: Relevance
“…At the population level, the most prominent patterns uncovered were a consistent distinction between Southern Mediterranean and northern continental Europeans (Seldin et al, 2006) and a clear separation of northern from southeastern Europeans (Bauchet et al, 2007). This is in line with mtDNA results and consistent with the clines observed using classical markers (Menozzi et al, 1978) and some mtDNA and Y-chromosome haplogroups (Rosser et al, 2000;Semino et al, 2000). These analyses also clearly separate Iberians including Basques as distinct from other Europeans but, in accordance with our results, they did not find specific affinities between Basques and the English and Irish, who cluster clearly with the continental Germans and Poles (Bauchet et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…At the population level, the most prominent patterns uncovered were a consistent distinction between Southern Mediterranean and northern continental Europeans (Seldin et al, 2006) and a clear separation of northern from southeastern Europeans (Bauchet et al, 2007). This is in line with mtDNA results and consistent with the clines observed using classical markers (Menozzi et al, 1978) and some mtDNA and Y-chromosome haplogroups (Rosser et al, 2000;Semino et al, 2000). These analyses also clearly separate Iberians including Basques as distinct from other Europeans but, in accordance with our results, they did not find specific affinities between Basques and the English and Irish, who cluster clearly with the continental Germans and Poles (Bauchet et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…The The fine structure of European populations SC Heath et al Table 4 Each horizontal line in the table shows the proportions of test samples originating from a given country that were assigned to each possible target country presence of a North -South gradient with which LCT is associated has been reported in several European studies using whole genome data, and a strong East -West gradient has also been reported in earlier studies. 7,11 Although it is interesting that the regions most highly associated with the North -South gradient are LCT, HLA and HERC2, it Figure 8 The scatter plot of the first two PCs of the European populations including the (German) Asthma cases using their estimated component weights.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The clustering approaches work on the basis of the presence of distinct genetic groups, and the probability of group membership of samples or, at a finer level, of chromosome blocks, can be estimated. These approaches and, in particular, the Bayesian clustering methods 8 have been widely used in population genetic studies because of the detailed information they provide on group membership and individual admixture.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work of Menozzi et al, 9 evidence has accumulated to show that allele frequencies vary within Europe, generating population structure at the continental scale. [10][11][12] Evidence of population structure accumulates at the scale of European countries [13][14][15][16][17][18] and even at a finer scale.…”
Section: Introductionmentioning
confidence: 99%